Utilization of Lemon Juice (Citrus limon L.) as an Alternative Substitute for Sodium Citrate in Blood Sedimentation Rate Examination - VINCENTIA ADE RIZKY; IKKE ELMALIA PUTRI; SAADAH SIREGAR (Medistra Medical Journal (MMJ), 2024)
Background: The erythrocyte sedimentation rate (LED) examination is a hematological test that describes the rate at which red blood cells settle in plasma, using 3.8% sodium citrate anticoagulant and is measured in mm/hour. Lemon (Citrus limon L.) is a plant with natural properties as a metal binding agent or chelating agent. Lemons contain vitamin C, citric acid, potassium, and limonene. Citric acid compounds are able to form complex bonds with metals because they have COOH and -OH functional groups. Apart from citric acid, lemons contain flavonoids which function as antiviral, anticancer and antiallergenic. Objective: To test whether lemon juice (Citrus limon L.) can be used as an alternative ingredient to replace sodium citrate in LED tests. Method: This research is an experiment using the Westergreen method. Results: LED examination with 3.8% sodium citrate produced a value of 10 mm/hour. Lemon juice with a concentration of 3.8% produces a value of 15 mm/hour, 10% produces a value of 10 mm/hour, 50% produces a value of 18 mm/hour, and 100% produces a value of 0 mm/hour. Conclusion: A lemon juice concentration of 10% showed results closest to the control, with similar LED values. Thus, lemon juice (Citrus limon L.) can serve as a substitute for sodium citrate in the LED test